2017
DOI: 10.1111/cogs.12493
|View full text |Cite
|
Sign up to set email alerts
|

Is the Lateralized Categorical Perception of Color a Situational Effect of Language on Color Perception?

Abstract: This study investigated whether and how a person's varied series of lexical categories corresponding to different discriminatory characteristics of the same colors affect his or her perception of colors. In three experiments, Chinese participants were primed to categorize four graduated colors-specifically dark green, light green, light blue, and dark blue-into green and blue; light color and dark color; and dark green, light green, light blue, and dark blue. The participants were then required to complete a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Somewhat more circumstantial evidence for the involvement of language in color perception comes from findings that in color discrimination tasks people show a larger between-category advantage in the right visual field (which projects to the left hemisphere) than in the left visual field [47,53,55,58,59], that verbal interference selectively affects between-category discrimination in the right visual field [55], and that the lateralization difference is already ob-served in early visual processing as measured by EEGs [60]. In related studies using functional neuroimaging, it has been found that color discrimination tasks evoke activity in cortical regions associated with naming (e.g., the left middle and superior temporal gyrus), that this activation is stronger for colors viewed in the right visual field [61], and that discriminating easy to name colors evoked greater activity in "naming" regions compared to discriminating harder-to-name colors [62].…”
Section: Effects Of Language On Discriminationmentioning
confidence: 99%
“…Somewhat more circumstantial evidence for the involvement of language in color perception comes from findings that in color discrimination tasks people show a larger between-category advantage in the right visual field (which projects to the left hemisphere) than in the left visual field [47,53,55,58,59], that verbal interference selectively affects between-category discrimination in the right visual field [55], and that the lateralization difference is already ob-served in early visual processing as measured by EEGs [60]. In related studies using functional neuroimaging, it has been found that color discrimination tasks evoke activity in cortical regions associated with naming (e.g., the left middle and superior temporal gyrus), that this activation is stronger for colors viewed in the right visual field [61], and that discriminating easy to name colors evoked greater activity in "naming" regions compared to discriminating harder-to-name colors [62].…”
Section: Effects Of Language On Discriminationmentioning
confidence: 99%
“…Therefore, the key notion leading the research on linguistic relativity is not whether minds are dependent on a given language but how verbal labels and categories interact with cognition across different contexts (Thierry, 2016;Zhong et al, 2017). Topics currently being studied include: cross-cultural comparisons (i.e., Boroditsky, 2001;Casasanto, 2008), the exploration of categorical effects under different interference conditions (i.e., Roberson and Davidoff, 2000;Gilbert et al, 2006;Winawer et al, 2007), and the time course of the effect, which informs whether perception or higher cognitive processes are involved (Mo et al, 2011;Clifford et al, 2012;He et al, 2014;Forder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We shall return to this point later. We finally note that CF2s may depend on culture and on scientific advances as demonstrated by (24).…”
Section: The Concept Of Cartesian Factorsmentioning
confidence: 87%